Evaluating interreligious peacebuilding and dialogue : methods and frameworks - Abu-Nimer, Mohammed, 1962-; Nelson, Renáta Katalin (KAICIID - beyond dialogue series ;, 2021)
In the emerging fields of religious and interreligious peacebuilding, the question of monitoring and evaluation is a challenging, yet necessary process. The need to develop comprehensive yet fitting evaluation models for religious and interreligious peacebuilding is not only important for donor interests, but also critical as a means of documenting and learning for peacebuilders themselves. Theories and best practices in monitoring and evaluation have become prevalent in many fields, yet the amount of literature on evaluating intercultural and, especially, religious and interreligious projects remains scant in comparison. This volume offers a unique contribution that not only looks at several of the challenges and implications faced by religious and interreligious peacebuilders but also provides concrete examples of new models and tools for monitoring and evaluating religious and interreligious peacebuilding projects. In doing so, this volume serves as a tool and point of reference for individuals and organizations developing and implementing interreligious dialogue and peacebuilding projects.